Novel Coronavirus SARS-CoV-2 (COVID-19) and Pregnancy: A Hypothetical View - Ahmed, RG (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2021)
The complications of the SARS-CoV-2 infection and its COVID-19 disease on mothers and their offspring are less known. This review aimed to determine the transmission, severity, and complications of SARS- CoV-2 infection during pregnancy. This review showed the influence of COVID-19 disease on neonatal neurogenesis. Owing medicines that were reported for the treatment of COVID-19 disease, this review suggested some control strategies like treatments (medicinal plants, antiviral therapy, cellular therapy, and immunotherapy), nutrition uptake, prevention, and recommendations. This overview showed that severe infection of SARS-CoV-2 during the early stage of pregnancy might increase the risk of stress, panic, and anxiety. This disorder can disturb the maternal immune system, and thus causing a neurodevelopmental disturbance. This hypothesis may be depending on the severity and intensity of the SARS-CoV-2 infection during pregnancy. However, vertical transmission of SARS-CoV-2 from dams to their fetuses is absent until now. During this global pandemic disease, maintaining safety during pregnancy, vaginal delivery, and breastfeeding may play a vital role in a healthy life for the offspring. Thus, international, and national organizations should be continuing for perinatal management, particularly during the next pandemic or disaster time.
Keywords: Treatment